Influence of sound and light combined conditions in urban environments on residents’ tolerance limits in pre sleep state - Yu, Yue; Feng, Danya; Zhang, Xin; Kang, Jian (Frontiers in Psychology, 2023)
To determine the interaction of sound and light pollution in urban residential environments at night, this paper comprehensively evaluates cross-visual and auditory sensory channels in the laboratory. Experimental variables include extremum and gradient, and the working state of the subjects was determined and verified. A subjective evaluation experiment on sound-light interaction was carried out by synthesizing real-world data. Results from the sound-light interaction experiment show that there are significant differences in the tolerance limits of subjects to different content sound variables. Among them, the traffic noise has the greatest impact on the tolerance limits of people, followed by birdsong and human voice. There is no difference in the tolerance limits of light pollution at different color temperatures. The tolerance limits of subjects will not be reduced due to the superposition of two interference variables: sound pollution and light pollution. Adding light pollution to sound pollution can increase the tolerance limits of subjects, while adding sound pollution to light pollution has no significant effect on the tolerance limits. The physiological and psychological differences between subjects may affect the performance differences of individual subjects in the interaction between sound and light.